A Comparative Transcriptional Landscape of Two Castor Cultivars Obtained by Single-Molecule Sequencing Comparative Analysis - Zhou, Yaxing; Zhu, Guoli; Wang, Yun; He, Zhibiao; Zhou, Wei (Frontiers in Genetics, 2021)
Background and Objectives: Castor (Ricinus communis L.) is an important non-edible oilseed crop. Lm type female strains and normal amphiprotic strains are important castor cultivars, and are mainly different in inflorescence structures and leaf shapes. To better understand the mechanisms underline these differences at the molecular level, we performed comparative transcriptional analysis. Results: A total of 76,068 and 44,223 non-redundant transcripts were obtained from high-quality transcripts of Lm type female strains and normal amphiprotic strains, respectively. In Lm female strain and normal amphiprotic strains 51,613 and 20,152 alternative splicing events were found, respectively. There were 13,239 transcription factors identified from the full-length transcriptomes. Comparative analysis showed great different gene expression of common and unique transcription factors between the two cultivars. Meanwhile, functional analysis of isoform was conducted. Full-length sequences were used as a reference genome, and short-read RNA sequencing analysis was performed to conduct differential gene analysis. Furthermore, the function of DEGs were performed to annotation analysis. Conclusions: The results revealed considerable difference and expression diversity between two cultivars, well beyond what was reported in previous studies, likely reflecting the differences in architecture between these two cultivars.